Oil palm empty fruit bunch fibres as sustainable acoustic absorber. (April 2017) - Or, Khai Hee; Putra, Azma; Selamat, Mohd Zulkefli
Highlights: Fibres from the oil palm empty fruit bunch (OPEFB) are studied for its sound absorption performance. OPEFB fibre sample with thickness of 40 mm can have absorption coefficient of 0.9 in average above 1 kHz. OPEFB fibre shows similar sound absorption performance with the commercial synthetic rock wools at the same thickness. Abstract: This paper discusses the utilisation of fibres from the oil palm empty fruit bunch (OPEFB) to be an alternative natural acoustic material. The study was carried out by fabricating samples from raw OPEFB fibres with different densities and thicknesses to observe their effects on the sound absorption performance. It has been demonstrated that the sound absorption performance can be improved by increasing the thickness of the sample and also by having optimum densities of fibres. In particular for lower frequencies, this can be achieved by introducing air cavity gap behind the fibre samples. Measurement of the normal incidence absorption coefficient in an impedance tube based on ISO 10534-2 found that the OPEFB fibres can have absorption coefficient of 0.9 on average above 1 kHz. The sound absorption performance of OPEFB fibres is also shown to be comparable to that of the commercial synthetic rock wools.